Method for detecting superhigh-purity germanium single crystal shallow-energy-level impurities

The method addresses the inability to detect shallow energy level impurities in high-purity germanium single crystals by using surface preparation and photothermal ionization spectroscopy, enabling effective impurity identification and purification for improved radiation detection.

CN119619110AActive Publication Date: 2025-03-14GRINM GUOJINGHUI NEW MATERIALS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411993080.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-14
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Current methods cannot detect shallow energy level impurities in high-purity germanium single crystals, which are crucial for their proper application in nuclear radiation detection systems.

Method used

A method involving surface preparation, metal indium film growth, and photothermal ionization spectroscopy to identify and quantify shallow energy level impurities in high-purity germanium single crystals, utilizing a sequence of steps including acid washing, electron beam evaporation, and thermal treatment to ensure good ohmic contact and impurity detection.

Benefits of technology

Enables the detection of shallow energy level impurities in high-purity germanium single crystals, improving their purity and guiding targeted purification steps, thus enhancing their suitability for nuclear radiation detection applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119619110A_ABST
    Figure CN119619110A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of single crystal impurity detection, and particularly discloses a method for detecting superhigh-purity germanium single crystal shallow-energy-level impurities. The method comprises the following steps: pretreating a germanium single crystal sample, sequentially carrying out photoetching, electron beam evaporation, annealing treatment and ohmic contact treatment to obtain a to-be-detected sample, putting the to-be-detected sample into a photothermal ionization spectrometer to obtain a photothermal ionization spectrum of the to-be-detected sample, comparing spectral line positions and intensities of elements, and calculating the concentration of the to-be-detected sample according to the spectral line positions and intensities of the elements. The impurity types and the concentration of the ultra-high-purity germanium single crystal shallow-energy-level impurities are obtained. According to the method, the metal indium film grows on the upper surface of the germanium single crystal, and shallow-energy-level impurities of the germanium single crystal can be detected in the photo-thermal ionization spectrometer without adding a conductive substance to the lower surface of the germanium single crystal. Meanwhile, the germanium single crystal is subjected to acid pickling treatment by utilizing an acid pickling solution with high nitric acid content, so that the germanium single crystal subjected to acid pickling can be tightly combined with the indium film evaporated by the electron beam, and the prepared sample with the indium film loaded on the upper surface has good ohmic contact characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of single crystal impurity detection, and specifically discloses a method for detecting shallow energy level impurities in an ultra-high purity germanium single crystal. Background Art

[0002] Ultra-high purity germanium materials can reach a purity of 13N. They are ultra-high purity metal materials and are new materials for germanium detection systems for nuclear radiation. The detection of nuclear radiation is particularly important in the application of nuclear technology. Nuclear radiation detectors with ultra-high purity germanium single crystals as the core material are widely used in military, quasi-military and nuclear civilian fields. In the military, they are mainly used for nuclear power safety monitoring, nuclear bombs and other nuclear military capability storage security monitoring. In the quasi-military, they are mainly used in customs, justice, progress and other aspects. In civilian use, they are mainly used for nuclear power plant safety monitoring and other aspects. For ultra-high purity germanium single crystals, impurity detection is a key step in whether ultra-high purity germanium single crystals can be used normally.

[0003] Impurities in ultra-high purity germanium single crystals are mainly divided into deep energy level impurities and shallow energy level impurities. The existing technology ([1] Gu Xiaoying, Zhao Qingsong, Niu Xiaodong, et al. Preparation and performance study of 13N ultra-high purity germanium single crystals [J]. Journal of Synthetic Crystals, 2024, 53(03): 497-502. DOI: 10.16553 / j.cnki.issn1000-985x.20240012.001.) has disclosed a method for detecting deep energy level impurities in ultra-high purity germanium single crystals. The article specifically discloses a method of sputtering a dot tin film on the front side of the germanium crystal as an electrode, connecting a copper sheet on the back side with tin foil and annealing it in an annealing environment below 300°C to obtain an ohmic electrode to be tested, and then performing deep energy level impurity detection. However, the ohmic electrode disclosed in the article, which is prepared by tinning the front of the germanium crystal and connecting the copper sheet with tin foil on the back of the germanium crystal through annealing, can only be used for deep energy level impurity detection, and cannot detect shallow energy level impurities in the germanium crystal. Based on this, developing a method for detecting shallow energy level impurities in ultra-high purity germanium single crystal is of great significance for the preparation and performance research of ultra-high purity germanium materials. Summary of the invention

[0004] In view of the lack of a detection method for shallow energy level impurities in ultra-high purity germanium single crystals in the prior art, the present invention provides a detection method for shallow energy level impurities in ultra-high purity germanium single crystals.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The first aspect of the present invention provides a method for detecting shallow level impurities in an ultra-high purity germanium single crystal, comprising the following steps: Step 1: Cut, grind, clean, blow dry, pickle, polish, clean and dry the germanium single crystal sample in sequence to obtain a pretreated sample, wherein the pickling solution is nitric acid and hydrofluoric acid in a volume ratio of (2-4):1. Wherein, the mass percentage concentration of the nitric acid is 60%-80%; the mass percentage concentration of the hydrofluoric acid is 30%-50%; Step 2, coating a positive photoresist on the surface of the pre-treated sample, drying, and photolithography to obtain a first treated sample; Step 3: growing a metal indium film on the upper surface of the first treated sample by electron beam evaporation in an inert atmosphere to obtain a second treated sample; Step 4: immersing the second treated sample in a polar organic solvent, stripping the photoresist layer, and performing solid-liquid separation to obtain a sample with a metal indium film loaded on the upper surface; annealing the sample with a metal indium film loaded on the upper surface in an inert atmosphere to obtain a sample to be tested; Step 5: Place the sample to be tested into a photothermal ionization spectrometer, test the photothermal ionization spectrum of the sample to be tested, compare the spectral line positions and intensities of the elements, and obtain the impurity types and concentrations of shallow energy level impurities in the ultra-high purity germanium single crystal.

[0007] The present invention grows a metal indium film on the upper surface of a germanium single crystal without adding a conductive material on the lower surface, so that the germanium single crystal can detect shallow energy level impurities in a photothermal ionization spectrometer, and also enables the germanium single crystal to have good ohmic contact characteristics at deep low temperatures. In addition, the present invention uses a pickling solution with a high nitric acid content to pickle the germanium single crystal, so that the pickled germanium single crystal can be closely combined with the indium film evaporated by an electron beam, ensuring that the prepared sample with the indium film loaded on the upper surface has good ohmic contact characteristics.

[0008] Preferably, in step 4, the annealing treatment specifically includes the following steps: The sample with the metal indium film loaded on the upper surface is heated from the first temperature to the second temperature, and the temperature is kept constant to complete one heating process. The above heating process is repeated multiple times until the temperature of the sample with the metal indium film loaded on the upper surface is 480°C-520°C, thereby obtaining the sample to be tested; the temperature range of the first temperature is 230°C-270°C; the second temperature is 45°C-55°C higher than the first temperature.

[0009] The invention uses a programmed temperature rising annealing treatment method to make the metal indium film tightly combined with the sample surface.

[0010] Preferably, the heating rate from the first temperature to the second temperature is 5°C / min-10°C / min; the insulation time is 50s-70s.

[0011] The present invention avoids the damage of the indium film due to excessively high temperature by limiting the first temperature, and also avoids the ineffective annealing due to excessively low temperature. In addition, the present invention further improves the tightness of the combination of the metal indium film and the sample by limiting the heating rate and the holding time.

[0012] Preferably, in step 1, the thickness of the cut germanium single crystal sample is 3 mm to 5 mm, and the dislocation density is 100 cm -2 -5000cm -2 Between, carrier concentration ≤ 2E10cm -3 .

[0013] The present invention can ensure that the single crystal sample has less impurities by limiting the thickness, dislocation density and carrier concentration of the single crystal sample, thereby ensuring the single crystal purity of the sample to be tested prepared subsequently.

[0014] Preferably, in step 1, the polishing time is 1 min-2 min.

[0015] The present invention improves the surface flatness of the single crystal sample by limiting the time of pickling and polishing.

[0016] Preferably, in step 2, the coating is performed by spin coating, and the rotation speed of the spin coating is 1000rpm-2000rpm.

[0017] The present invention limits the coating method to spin coating and limits the rotation speed of the spin coating to ensure the flatness of the coating.

[0018] Preferably, in step 2, the coating thickness of the positive photoresist is 1.5 μm-2 μm.

[0019] The present invention limits the coating thickness to spin coating, thereby preventing the coating thickness of the photoresist from being too thick or too thin, thereby causing poor photolithography effect.

[0020] Preferably, in step 2, the drying temperature is 90° C.-110° C., and the drying time is 1 min-3 min.

[0021] The present invention can ensure excellent drying effect of the photoresist by limiting the drying temperature and time.

[0022] Preferably, in step 2, the temperature of the photolithography is 25° C.-30° C., and the time of the photolithography is 50 s-80 s.

[0023] The present invention can ensure excellent photolithography effect by limiting the temperature and time of photolithography.

[0024] Preferably, in step three, the temperature of the electron beam evaporation is 160°C-200°C.

[0025] Preferably, in step three, the thickness of the metal indium film is 100-150 nm.

[0026] The present invention can ensure that the sample to be tested has good ohmic contact characteristics by limiting the temperature of electron beam evaporation and the thickness of the metal indium film.

[0027] Preferably, in step 4, the polar organic solvent is acetone.

[0028] The present invention can ensure that the sample to be tested has good ohmic contact characteristics by limiting the type of polar organic solvent.

[0029] Preferably, in step five, the test conditions of the photothermal ionization spectrum are: vacuum degree is less than 0.3 kPa, and temperature is 4K-10K.

[0030] The present invention can ensure the detection of shallow energy level impurities of ultra-high purity germanium single crystal by limiting the test conditions of the photothermal ionization spectrum.

[0031] Preferably, the photothermal ionization spectrometer includes a Fourier transform infrared spectrometer, a Michelson interferometer, a refrigeration system, a temperature control measurement system, a preamplifier, a filter, an oscilloscope and a computer system.

[0032] The present invention analyzes the types and relative contents of shallow energy level impurities in a single crystal by limiting the device of a photothermal ionization spectrometer, thereby solving the problem that the prior art cannot detect and confirm shallow energy level impurities in ultra-high purity germanium single crystals.

[0033] Beneficial effects: 1. The present invention grows a metal indium film on the upper surface of a germanium single crystal, and there is no need to add a conductive material on the lower surface, so that the germanium single crystal can detect shallow energy level impurities in a photothermal ionization spectrometer, and also enables it to have good ohmic contact characteristics at deep low temperatures. In addition, the present invention uses a pickling solution with a high nitric acid content to pickle the germanium single crystal, so that the pickled germanium single crystal can be tightly combined with the indium film evaporated by an electron beam, ensuring that the prepared sample with an indium film loaded on the upper surface has good ohmic contact characteristics. The present invention can realize shallow energy level impurity detection using the above-mentioned sample with an indium film loaded on the upper surface, solving the problem that the prior art cannot detect and confirm shallow energy level impurities in ultra-high purity germanium single crystals. 2. The present invention utilizes grinding and pickling and polishing methods to pretreat single crystal samples, which can ensure that the surface of the pretreated samples is flat, free of cutting damage and scratches. In addition, the present invention limits the pickling to a pickling solution with a high nitric acid content, which can enable the pickled germanium single crystal to be tightly combined with the indium film evaporated by an electron beam, ensuring that the prepared sample with an indium film loaded on the upper surface has good ohmic contact characteristics. 3. By confirming the shallow energy level impurities, the present invention can effectively guide the improvement of the front-end process of single crystal production, remove impurities in a targeted manner, and thus improve the purity of single crystals, providing technical support for the mass production of 13N ultra-high purity germanium single crystals, and providing a new testing basis for the preparation of 13N ultra-high purity germanium single crystals. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The process flow chart of detecting shallow energy level impurities of ultra-high purity germanium single crystal in Example 1;

[0035] Figure 2 A schematic diagram of the sample to be tested provided in Example 1;

[0036] Figure 3 This is a Hall test curve diagram of the sample to be tested at liquid nitrogen temperature in Example 1;

[0037] Figure 4 This is the system block diagram of the photothermal ionization spectrometer;

[0038] Figure 5 This is the photothermal ionization spectrum of the main shallow-level impurities of the sample to be tested in Example 1 at 7.5K. DETAILED DESCRIPTION

[0039] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] The invention provides a method for detecting shallow energy level impurities in an ultra-high purity germanium single crystal. The method comprises the following steps: pre-treating a single crystal sample, sequentially performing photolithography, electron beam evaporation, annealing treatment and ohmic contact treatment to obtain a sample to be tested, placing the sample to be tested in a photothermal ionization spectrometer to obtain a photothermal ionization spectrum of the sample to be tested, and comparing the spectral line positions and intensities of the elements to obtain the impurity types and concentrations of the shallow energy level impurities in the ultra-high purity germanium single crystal.

[0041] In the present invention, the system block diagram of the photothermal ionization spectrometer is as follows Figure 4 As shown by Figure 4 It can be seen that the photothermal ionization spectrometer of the present invention includes a Fourier transform infrared spectrometer, a Michelson interferometer, a refrigeration system, a temperature control and measurement system, a preamplifier, a filter, an oscilloscope and a computer system.

[0042] Example 1

[0043] A method for detecting shallow-level impurities in an ultra-high purity germanium single crystal comprises the following steps: Step 1: Select a size of 7mm×7mm×3mm, with a carrier concentration of ≤2E10cm -3 , the dislocation density is at 2300cm -2 The P-type germanium single crystal sample is carefully ground on a smooth and flat glass plate using diamond abrasive powder from coarse to fine, and an appropriate amount of deionized water is added during grinding, and the sample surface is ground until there is no cutting damage and scratches, and the surface is flat, and then it is rinsed with ultrapure water and blown dry with nitrogen, and then the dried P-type single crystal sample is polished for 2 minutes with an acid solution of a mass percentage concentration of 70% nitric acid solution and a mass percentage concentration of 40% hydrofluoric acid solution in a volume ratio of 3:1, until the sample surface is flat and bright, and the polished sample is cleaned with ultrapure water until it is neutral, and then it is blown dry with nitrogen to obtain a pretreated sample; Step 2: Spin coating a layer of B1500 positive photoresist on the surface of the pre-treated sample, bake at 100° C. for 2 min after spin coating, and then perform photolithography on the sample to expose the part where the front electrode needs to be grown, to obtain a first treated sample; wherein the spin coating speed is 1000 rpm; Step 3: In an inert atmosphere, place the first treated sample in an electron beam evaporation device, add metal indium, and evacuate to 5×10 -4 below Pa, growing a metal film on the surface of the first treated sample by electron beam evaporation to obtain a second treated sample; Step 4, immerse the second treated sample in acetone for 5 minutes, use a disposable pipette to absorb acetone to impact the sample surface, peel off the photoresist and the metal above, separate the solid and liquid, and obtain a sample with a surface-loaded metal indium film; heat the sample with a surface-loaded metal indium film to 300°C at a heating rate of 5°C / min under an argon atmosphere at 250°C, keep warm for 60s, then heat it to 350°C at a heating rate of 5°C / min, keep warm for 60s, then heat it to 400°C at a heating rate of 5°C / min, keep warm for 60s, then heat it to 450°C at a heating rate of 5°C / min, keep warm for 60s, then heat it to 500°C at a heating rate of 5°C / min, keep warm for 60s, and obtain a sample to be tested; use a Hall tester to test the IV curve of the sample at room temperature and liquid nitrogen temperature, and prepare for photothermal ionization spectroscopy test after proving that the sample ohmic contact is qualified; Step 5: Place the sample to be tested into a photothermal ionization spectrometer, place the probe on the ohmic electrode, evacuate the sample chamber to 3 mbar, then turn on the refrigerator to cool down to 4K, and then test. First, test the photothermal ionization spectrum at different temperature values ​​in the range of 5K-10K (each time the temperature step is increased by 0.5K) to determine the optimal test temperature, and then select the curve with stable excited state signal, relatively large intensity, and relatively small noise for analysis.

[0044] The current-voltage characteristic test of the sample to be tested in Example 1 is carried out, and the test results are as follows: Figure 3 As shown. Figure 3 It can be seen that the current-voltage (IV) characteristic of the sample to be tested in Example 1 is linear, which can prove that the sample to be tested in Example 1 also has good ohmic characteristics at low temperatures and can meet the requirements of photothermal ionization spectroscopy testing. The sample to be tested in Example 1 was subjected to photothermal ionization spectroscopy detection of main shallow energy level impurities, and the test results are as follows: Figure 5 As shown. Figure 5 It can be seen that the wavelength range corresponding to each excited state transition of the shallow impurity, the wavelengths corresponding to different peak heights of the test data are roughly divided into two groups of spectral line systems, corresponding to the transition of the shallow acceptor impurity from the ground state to the excited state, it can be known that the two shallow acceptor impurities are B and Al, and the concentration ratio of the two impurities is estimated according to the relative ratio of the spectral line intensity of the two impurities, and then according to the net impurity concentration tested by the Hall test, according to the relative ratio of the spectral line intensity of the two, their approximate content can be inferred. It can be seen from this that the detection method provided in Example 1 of the present invention can analyze the types and relative contents of shallow energy level impurities in single crystals, solving the problem that the prior art cannot detect and confirm shallow energy level impurities in ultra-high purity germanium single crystals.

[0045] Example 2

[0046] A method for detecting shallow-level impurities in an ultra-high purity germanium single crystal comprises the following steps: Step 1: Select a size of 8mm×8mm×4mm, with a carrier concentration of ≤2E10cm -3 , the dislocation density is 150cm -2 The P-type germanium single crystal sample is carefully ground on a smooth and flat glass plate using diamond abrasive powder from coarse to fine, and an appropriate amount of deionized water is added during grinding, and the sample surface is ground until there is no cutting damage and scratches, and the surface is flat, and then it is rinsed with ultrapure water and blown dry with nitrogen, and then the dried P-type single crystal sample is polished for 2 minutes with an acid solution of a mass percentage concentration of 70% nitric acid solution and a mass percentage concentration of 40% hydrofluoric acid solution in a volume ratio of 3:1, until the sample surface is flat and bright, and the polished sample is cleaned with ultrapure water until it is neutral, and then it is blown dry with nitrogen to obtain a pretreated sample; Step 2: Spin coating a layer of B1500 positive photoresist on the surface of the pre-treated sample, bake at 100° C. for 2 min after spin coating, and then perform photolithography on the sample to expose the part where the front electrode needs to be grown, to obtain a first treated sample; wherein the spin coating speed is 2000 rpm; Step 3: In an inert atmosphere, place the first treated sample in an electron beam evaporation device, add metal indium, and evacuate to 5×10-4 below Pa, growing a metal film on the surface of the first treated sample by electron beam evaporation to obtain a second treated sample; Step 4, immerse the second treated sample in acetone for 5 minutes, use a disposable pipette to absorb acetone to impact the sample surface, peel off the photoresist and the metal above, separate the solid and liquid, and obtain a sample with a metal indium film on the surface; heat the sample with a metal indium film on the surface to 320°C at a heating rate of 10°C / min in an argon atmosphere at 270°C, keep warm for 70s, then heat it to 370°C at a heating rate of 5°C / min, keep warm for 70s, then heat it to 420°C at a heating rate of 5°C / min, keep warm for 70s, then heat it to 470°C at a heating rate of 5°C / min, keep warm for 70s, then heat it to 520°C at a heating rate of 5°C / min, keep warm for 70s, and obtain a sample to be tested; use a Hall tester to test the IV curve of the sample at room temperature and liquid nitrogen temperature, and prepare for photothermal ionization spectroscopy test after proving that the sample ohmic contact is qualified; Step 5: Place the sample to be tested into a photothermal ionization spectrometer, place the probe on the ohmic electrode, evacuate the sample chamber to 3 mbar, then turn on the refrigerator to cool down to 4K, and then test. First, test the photothermal ionization spectrum at different temperature values ​​in the range of 5K-10K (each time the temperature step is increased by 0.5K) to determine the optimal test temperature, and then select the curve with stable excited state signal, relatively large intensity, and relatively small noise for analysis.

[0047] Example 3

[0048] A method for detecting shallow-level impurities in an ultra-high purity germanium single crystal comprises the following steps: Step 1: Select a size of 8mm×7mm×3mm, with a carrier concentration of ≤2E10cm -3 , the dislocation density is 5000cm -2 The P-type germanium single crystal sample is carefully ground on a smooth and flat glass plate using diamond abrasive powder from coarse to fine, and an appropriate amount of deionized water is added during grinding, and the sample surface is ground until there is no cutting damage and scratches, and the surface is flat, and then it is rinsed with ultrapure water and blown dry with nitrogen, and then the dried P-type single crystal sample is polished for 2 minutes with an acid solution of a mass percentage concentration of 70% nitric acid solution and a mass percentage concentration of 40% hydrofluoric acid solution in a volume ratio of 3:1, until the sample surface is flat and bright, and the polished sample is cleaned with ultrapure water until it is neutral, and then it is blown dry with nitrogen to obtain a pretreated sample; Step 2: Spin coating a layer of B1500 positive photoresist on the surface of the pre-treated sample, bake at 100° C. for 2 min after spin coating, and then perform photolithography on the sample to expose the part where the front electrode needs to be grown, to obtain a first treated sample; wherein the spin coating speed is 1500 rpm; Step 3: In an inert atmosphere, place the first treated sample in an electron beam evaporation device, add metal indium, and evacuate to 5×10 -4 below Pa, growing a metal film on the surface of the first treated sample by electron beam evaporation to obtain a second treated sample; Step 4, immerse the second treated sample in acetone for 5 minutes, use a disposable pipette to absorb acetone to impact the sample surface, peel off the photoresist and the metal above, separate the solid and liquid, and obtain a sample with a metal indium film on the surface; heat the sample with a metal indium film on the surface to 280°C at a heating rate of 5°C / min under an argon atmosphere at 230°C, keep warm for 60s, then heat it to 330°C at a heating rate of 5°C / min, keep warm for 60s, then heat it to 380°C at a heating rate of 5°C / min, keep warm for 60s, then heat it to 430°C at a heating rate of 5°C / min, keep warm for 60s, then heat it to 480°C at a heating rate of 5°C / min, keep warm for 60s, and obtain a sample to be tested; use a Hall tester to test the IV curve of the sample at room temperature and liquid nitrogen temperature, and prepare for photothermal ionization spectroscopy test after proving that the sample ohmic contact is qualified; Step 5: Place the sample to be tested into a photothermal ionization spectrometer, place the probe on the ohmic electrode, evacuate the sample chamber to 3 mbar, then turn on the refrigerator to cool down to 4K, and then test. First, test the photothermal ionization spectrum at different temperature values ​​in the range of 5K-10K (each time the temperature step is increased by 0.5K) to determine the optimal test temperature, and then select the curve with stable excited state signal, relatively large intensity, and relatively small noise for analysis.

[0049] Example 4

[0050] A method for detecting shallow-level impurities in an ultra-high purity germanium single crystal comprises the following steps: Step 1: Select a size of 8mm×8mm×3mm, with a carrier concentration of ≤2E10cm -3 , dislocation density is 100-5000cm -2The N-type germanium single crystal sample is carefully ground on a smooth and flat glass plate using diamond abrasive powder from coarse to fine, and an appropriate amount of deionized water is added during grinding, and the sample surface is ground until there is no cutting damage and scratches, and the surface is flat, and then it is rinsed with ultrapure water and blown dry with nitrogen, and then the dried P-type single crystal sample is polished for 2 minutes with an acid solution of a mass percentage concentration of 70% nitric acid solution and a mass percentage concentration of 40% hydrofluoric acid solution in a volume ratio of 3:1, until the sample surface is flat and bright, and the polished sample is cleaned with ultrapure water until it is neutral, and then it is blown dry with nitrogen to obtain a pretreated sample; Step 2: Spin coating a layer of B1500 positive photoresist on the surface of the pre-treated sample, bake at 100° C. for 2 min after spin coating, and then perform photolithography on the sample to expose the part where the front electrode needs to be grown, to obtain a first treated sample; wherein the spin coating speed is 1500 rpm; Step 3: In an inert atmosphere, place the first treated sample in an electron beam evaporation device, add metal indium, and evacuate to 5×10 -4 below Pa, growing a metal film on the surface of the first treated sample by electron beam evaporation to obtain a second treated sample; Step 4, immerse the second treated sample in acetone for 5 minutes, use a disposable pipette to absorb acetone to impact the sample surface, peel off the photoresist and the metal above, separate the solid and liquid, and obtain a sample with a surface-loaded metal indium film; heat the sample with a surface-loaded metal indium film to 300°C at a heating rate of 5°C / min under an argon atmosphere at 250°C, keep warm for 60s, then heat it to 350°C at a heating rate of 5°C / min, keep warm for 60s, then heat it to 400°C at a heating rate of 5°C / min, keep warm for 60s, then heat it to 450°C at a heating rate of 5°C / min, keep warm for 60s, then heat it to 500°C at a heating rate of 5°C / min, keep warm for 60s, and obtain a sample to be tested; use a Hall tester to test the IV curve of the sample at room temperature and liquid nitrogen temperature, and prepare for photothermal ionization spectroscopy test after proving that the sample ohmic contact is qualified; Step 5: Place the sample to be tested into a photothermal ionization spectrometer, place the probe on the ohmic electrode, evacuate the sample chamber to 3 mbar, then turn on the refrigerator to cool down to 4K, and then test. First, test the photothermal ionization spectrum at different temperature values ​​in the range of 5K-10K (each time the temperature step is increased by 0.5K) to determine the optimal test temperature, and then select the curve with stable excited state signal, relatively large intensity, and relatively small noise for analysis.

[0051] It can be seen from Examples 1-4 that the detection method provided by the present invention is capable of analyzing the types and relative contents of shallow energy level impurities in different crystal types (P-type single crystal and N-type single crystal) of germanium single crystal, thereby solving the problem that the prior art is unable to detect and confirm shallow energy level impurities in ultra-high purity germanium single crystal.

[0052] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for detecting shallow level impurities in ultra-high purity germanium single crystal, characterized in that: The steps include: Step 1, cutting, grinding, cleaning, blowing, pickling, polishing, cleaning and drying the germanium single crystal sample in sequence to obtain a pretreated sample, wherein the pickling solution is nitric acid and hydrofluoric acid in a volume ratio of (2-4):1, wherein the mass percentage concentration of the nitric acid is 60%-80%; the mass percentage concentration of the hydrofluoric acid is 30%-50%; Step 2, coating a positive photoresist on the surface of the pre-treated sample, drying, and photolithography to obtain a first treated sample; Step 3: growing a metal indium film on the upper surface of the first treated sample by electron beam evaporation in an inert atmosphere to obtain a second treated sample; Step 4: immersing the second treated sample in a polar organic solvent, stripping the photoresist layer, and performing solid-liquid separation to obtain a sample with a metal indium film loaded on the upper surface; annealing the sample with a metal indium film loaded on the upper surface in an inert atmosphere to obtain a sample to be tested; Step 5: placing the sample to be tested into a photothermal ionization spectrometer to obtain the impurity types and concentrations of shallow energy level impurities in the ultra-high purity germanium single crystal.

2. The method for detecting shallow level impurities in ultra-high purity germanium single crystal according to claim 1, characterized in that: In step 4, the annealing treatment specifically includes the following steps: The sample with the metal indium film loaded on the upper surface is heated from the first temperature to the second temperature, and the temperature is kept constant to complete one heating process. The above heating process is repeated multiple times until the temperature of the sample with the metal indium film loaded on the upper surface is 480°C-520°C, thereby obtaining the sample to be tested; the temperature range of the first temperature is 230°C-270°C; the second temperature is 45°C-55°C higher than the first temperature.

3. The method for detecting shallow level impurities in ultra-high purity germanium single crystal according to claim 2, characterized in that: The heating rate from the first temperature to the second temperature is 5°C / min-10°C / min; the insulation time is 50s-70s.

4. The method for detecting shallow level impurities in ultra-high purity germanium single crystal according to claim 1, characterized in that: In step 1, the thickness of the cut germanium single crystal sample is 3 mm-5 mm, the dislocation density is between 100 cm-2 and 5000 cm-2, and the carrier concentration is ≤2E10 cm-3; and / or In step 1, the polishing time is 1 min-2 min.

5. The method for detecting shallow level impurities in ultra-high purity germanium single crystal according to claim 1, characterized in that: In step 2, the coating is performed by spin coating at a speed of 1000 rpm to 2000 rpm; and / or In step 2, the coating thickness of the positive photoresist is 1.5 μm-2 μm.

6. The method for detecting shallow level impurities in ultra-high purity germanium single crystal according to claim 1, characterized in that: In step 2, the drying temperature is 90°C-110°C, and the drying time is 1 min-3 min; and / or In step 2, the temperature of the photolithography is 25° C.-30° C., and the time of the photolithography is 50s-80s.

7. The method for detecting shallow level impurities in ultra-high purity germanium single crystal according to claim 1, characterized in that: In step 3, the temperature of the electron beam evaporation is 160° C.-200° C.; and / or In step three, the thickness of the metal indium film is 100nm-150nm.

8. The method for detecting shallow level impurities in ultra-high purity germanium single crystal according to claim 1, characterized in that: In step 5, the test conditions of the photothermal ionization spectrum are: vacuum degree <0.3 KPa, temperature 4K-10K.

Citation Information

Patent Citations

  • Miniature probe station for Hall test of high-purity germanium single crystal and test method

    CN116087571A

  • Process for preparing high-purity germanium single crystal by Czochralski method

    CN118756326A

  • Impurity concentration measuring method

    JP2000195917A

  • Method and apparatus for measuring shallow level in silicon single crystal

    JP2002350331A

  • Method of determination of addition composition and quantity in non-metallic media

    SU857794A1